User satisfaction model to measure open government data usage - Ahmed, Mohammed Shihab (2020)
The open government data (OGD) initiative is presented by the government of any country to achieve promotion of transparency, social control and citizens participation in policy making. The use of OGD in Malaysia is still in its early stage and facing problems such as less participation, security issues, and lack of awareness. While most of the research in Information Communication Technology (ICT) that underpinned by Expectation Confirmation Theory (ECT) are focused on user satisfaction and determination of users’ reuse intention, this study focus on the direct antecedents of OGD users’ intention to use and its influence on OGD users’ satisfaction, as this research is still scarce. This research aims to examine ECT model on users’ satisfaction mediated by the intention to use the open government data (OGD). The objectives of this research are in three folds; (1) to design an integrated ECT and TAM models for explaining OGD satisfaction, (2) to examine the mediating role of citizens’ behavioural intention between the expectations, confirmation, perceived performance, incentive on usage, perceived risk and citizen’s satisfaction of open government data, (3) and to validate the impact of incentives on usage and perceived risk in explaining the new ECT model in the OGD context. Data were collected from 250 samples of OGD users in Malaysia. Empirical evidences were gathered through self-administered questionnaires using the Likert scale. The data were analysed using Partially Least Square Structural Equation Modelling (PLS-SEM) in order to test the model. The final model was verified by experts in the area. Results revealed that expectation has significant relationship with confirmation, but perceived performance showed insignificant relationship with confirmation which serves as a unique finding. Additionally, confirmation, expectation, perceived performance, incentive on usage and perceived risk has significant relationship with intention to use OGD. Meanwhile, the analysis proved that the intention to use mediates the relationship between confirmation, expectation, perceived performance, incentive on usage, perceived risk and satisfaction on use of OGD. This study suggests that the user’s expectations on OGD must be met in creating stronger intention and satisfaction. The implications of the study are to improve data service quality, support innovative services development, increase data transparency, and boost up potential investment.